Packaging Metal Atomic Clusters for Universal and Robust Protection through Cluster Beam Process - Siqi Lu; Zixiang Zhao; Jinsen Han; Jun Wang; Yongxin Zhang; Yu Du; Fangyu Guo; Zhichao Wang; Shenghui Wang; Sichen Tang; Kuojuei Hu; Jianguo Wan; et al. (Advanced Science)
Abstract Size‐selected gas‐phase aggregated metal clusters have long been considered as embryos of materials. However, a significant proportion of these clusters are susceptive to damage when exiting vacuum. Consequently, effective protection is highly desirable. Here a cluster packaging and protection strategy is presented based on controllable cluster beam implantation into polymethyl methacrylate (PMMA). In this strategy, the size selection of gas‐phase clusters and the synergistic heating of PMMA during implantation are combined, thereby achieving nondestructive packaging of atomically precise cluster under soft‐landing conditions. The packaged clusters exhibit robust and universal protection. Robustness is reflected in the unaltered oxidation resistance of Mo clusters after exposure to air for over 30 days, as well as the effective agglomeration resistance at temperatures up to 100 °C or in liquid. Universality is demonstrated by the successful protection of a wide range of size‐selected clusters, including Mo clusters ranging from Mo2057 to Mo6, and Ta2057, Cu923, W55, (Re–Mo)147 clusters. This protection is attributed to both a stable, albeit weak PMMA‐Mo bonding, forming Mo─O─C─C species that stabilize the clusters, and the direct implantation of gas‐phase cluster into solid‐phase PMMA. This helps pave the way for further investigation and applications of gas‐phase metal clusters.